2007
DOI: 10.5897/ajb2007.000-2331
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel generation from oleaginous yeast Rhodotorula glutinis with xylose assimilating capacity

Abstract: This study explored a strategy to convert agricultural and forestry residues into microbial lipid, which could be further transformed into biodiesel. Among the 250 yeast strains screened for xylose assimilating capacity, eight oleaginous yeasts were selected by Sudan Black B test. The lipid content of these 8 strains was determined by soxhlet extraction method. One strain (T216) was found to produce lipids up to 36.6%, and it was identified as Rhodotorula glutinis. The optimal fermentation conditions were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…An aspect considered is xylose used carbon source in the medium with a C/N ratio of 100:1, while glucose was used as a carbon source in the medium with a C/N ratio 2:1. In this regard, it has been reported that the R. glutinis strain T216 produced 36.6% of lipids, whose optimal conditions occurred when glucose was used as a carbon source, accumulating a higher concentration of lipids of 49.25% concerning the cellular biomass (Dai et al, 2007). Glucose and xylose can be used by oily yeasts isolated from soil or other natural sources to produce lipids.…”
Section: Discussionmentioning
confidence: 99%
“…An aspect considered is xylose used carbon source in the medium with a C/N ratio of 100:1, while glucose was used as a carbon source in the medium with a C/N ratio 2:1. In this regard, it has been reported that the R. glutinis strain T216 produced 36.6% of lipids, whose optimal conditions occurred when glucose was used as a carbon source, accumulating a higher concentration of lipids of 49.25% concerning the cellular biomass (Dai et al, 2007). Glucose and xylose can be used by oily yeasts isolated from soil or other natural sources to produce lipids.…”
Section: Discussionmentioning
confidence: 99%
“…One gram from different samples (rotten fruits, pickles, plant leaves, and sugar cane juice) was added to 10 ml of saline solution and subsequently followed by a tenfold serial dilution. An aliquot of 1 ml from each dilution was spread onto plates containing isolation medium which includes (g/L): glucose (20), (NH 4 ) 2 SO 4 (2), KH 2 PO 4 (0.5), MgSO 4 .7H 2 O (0.2), CaCl 2 .2H 2 O (0.1), and 2% agar in the presence of 3.3 ml of streptomycin solution (10.000 U/ml) [ 18 ]. The plates were incubated at 28 °C for 48 h, and then those containing isolated colonies with the morphology typical of yeasts were used for further study.…”
Section: Methodsmentioning
confidence: 99%
“…The high producer yeast isolates were activated in an inoculation medium, containing (g/L): glucose (40), peptone (5), yeast extract (15) [ 18 ]. The inoculum was prepared by transferring one loop full of 24-h yeast culture grown on YEPD agar slant to Erlenmeyer flask containing 50 ml inoculum medium and incubated on a rotary shaker at 150 rpm and 28 °C for 24 h. The cell concentration of inoculum was monitored by counting in a Neubauer chamber until reaching approximately 1 × 10 8 cells/ml [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…By this strategy, translocation of TAGs ensures availability of carbon throughout the mycelium (Bago et al, 2002). Specific strains of oleaginous microbes were found to be associated with a wide range of habitats including flower, rainforest trees, lawns, mangrove leaves, dairy products, sponges, and zooplankton (Dai et al, 2007;Li et al, 2012;Unagul et al, 2017). In general, habitats with high C:N ratio were reported to be better for microbial lipid accumulation (Li et al, 2012).…”
Section: Oleaginous Ectosymbiotic Microorganismsmentioning
confidence: 99%
“…Oleaginous yeast strain Rhodotorula glutinis isolated from leaves of Rose centifolia accumulated intracellular lipid up to 36.6% while utilizing xylose as a sole carbon source (Dai et al, 2007). Another study by Duarte et al (2013) isolated oleaginous yeast strain of Candida sp.…”
Section: Oleaginous Ectosymbiotic Microorganismsmentioning
confidence: 99%